PENINGKATAN PENDAPATAN MELALUI PENDAMPINGAN PENGEMBANGAN USAHA MIKRO EMPING MELINJO DIKELURAHAN KANDANG KOTA BENGKULU - Dri Asmawanti S; Heni Nopianti; Afdhal Kurniawan Mainil (Universitas Bengkulu, 2018)
This community service activitiy aims to improve the capacity, knowledge and skills in various aspects of micro scale enterprise (MSE) or business of gnetum chips (production, management and law). In addition, the goal is improving the quantity and quality of produced gnetum chips. The training has been done to diversify the products processed chips gnetum IE cookies crackers and chips caramelized on the Group micro scale business of Rafflesia and Cempaka in Bengkulu City. In management aspects of the business, it has been implemented various activities that can enhance the knowledge and skills of the partners in managing their business, such as business management and computerized marketing training. Lastly, in terms of the law, it has been implemented mentoring of legal permission to partner in order to register their business to P-IRT. Keywords: mikro scale enterprise, genum (emping), business, income